2023
DOI: 10.2147/iprp.s395322
|View full text |Cite
|
Sign up to set email alerts
|

Community Pharmacists’ Views on the Early Stages of Implementation of a National Pilot Independent Prescribing Service in Wales: A Qualitative Study

Abstract: Background A pilot Independent Prescribers’ Service (IPS) was introduced in 13 community pharmacies across Wales in June 2020. Independent Pharmacist Prescribers (IPPs) could prescribe in the areas of management of acute conditions, contraception, or opioid withdrawal, as agreed with local commissioners. Access to the patients’ medical records was provided via Choose Pharmacy , the national community pharmacy IT platform. Objective To explore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…These will be of particular importance with the emergence of pharmacist prescriber status on graduation. Several earlier studies have reported early career pharmacists' cautious approaches to considering prescribing practice [45,46]. The need for advances in digitalisation to further support implementation are particularly interesting with reports of the integration of the services to improve access to clinical information and enhance prescribing [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…These will be of particular importance with the emergence of pharmacist prescriber status on graduation. Several earlier studies have reported early career pharmacists' cautious approaches to considering prescribing practice [45,46]. The need for advances in digitalisation to further support implementation are particularly interesting with reports of the integration of the services to improve access to clinical information and enhance prescribing [46,47].…”
Section: Discussionmentioning
confidence: 99%